일방향응고한 GTD-111 초내열합금의 황 함량에 따른 미세조직 및 고온 기계적 특성 - 강동수; Dong-soo Kang; 이형수; Hyungsoo Lee; 윤대원; Dae Won Yun; 정희원; Hi Won Jeong; 유영수; Young-soo Yoo; 서성문; Seong-moon Seo (대한금속·재료학회지, 60(10), 2022)
The influence of trace amounts of sulfur (S) on the microstructural evolution, tensile and creep properties in directionally solidified (DS) Ni-based superalloy GTD-111 were systematically investigated. Doping of S in the range of < 1 to 154 ppm resulted in the formation of a Ti 2 SC-type carbosulfide phase near the coarse eutectic γ/γ and η (eta, Ni 3 Ti) phases in interdendritic regions and grain boundaries (GB). The morphology of the Ti 2 SC was found to change from discrete particles to curved and elongated (film-like) shapes with increasing S content. The measurement of GB line fractions revealed that the GB fraction of Ti 2 SC increases with S content and reaches about 20% in 154 ppm S alloy. Tensile test results showed that the tensile properties at room temperature were not influenced by S doping, while the tensile elongation at 650-980 ℃ significantly decreased with increasing S content. The creep life and rupture elongation were also found to decrease with S content. The normalized creep life of 154 ppm S alloy was only in the 69%-74% range, compared to that of < 1 ppm S alloy. Careful microstructural observation of the fracture surface and longitudinal section of the creep ruptured 154 ppm S alloy revealed that Ti 2 SC plays a significant role in crack formation at the matrix γ/ Ti 2 SC interface, and leads to brittle facet-like traces on the fracture surface. It was concluded from these results that the formation of film-like Ti 2 SC in high S alloys might be responsible for the reduction in creep life and rupture elongation of DS GTD-111 alloy. (Received 6 July, 2022; Accepted 29 July 2022)